The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1002/ddr.430240404
|View full text |Cite
|
Sign up to set email alerts
|

Novel effects of memantine in antagonizing acute aldicarb toxicity: Mechanistic and applied considerations

Abstract: min, respectively, prior to aldicarb (0.4 mg/kg), provided complete protection. Therapeutic administration of these two antidotes in combination also completely reversed the clinical signs of intoxication. It is suggested that memantine antagonized the aldicarb acute toxicity by protection/reactivation of activities of AChE and CarbE and reversible blockade of hyperneuromuscular transmission, in addition to muscarinic ACh receptor blockade by atropine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…These findings are further strengthened by the recent observations with rivastigmine in in vitro and in vivo studies [Enz and Gentsch, 2004]. However, numerous in vivo studies have demonstrated that at higher doses MEM attenuates AChE inhibition against several organophosphate (OP) nerve agents (soman, sarin, tabun, and VX), an OP prototype compound (DFP) and an insecticide (methyl parathion), and carbamate insecticides (carbofuran, aldicarb, oxamyl, and methomyl) [Gupta and Kadel, 1989, 1990, 1991Gupta and Dettbarn, 1992;McLean et al, 1992;Gupta, 1994;Gupta and Goad, 2000]. Both in vitro and in vivo studies [McLean et al, 1992;Stojiljkovic et al, 2002;Antonijevic et al, 2002] further confirmed that MEM pretreatment protects AChE in rat and mice brain against soman-induced AChE inhibition.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These findings are further strengthened by the recent observations with rivastigmine in in vitro and in vivo studies [Enz and Gentsch, 2004]. However, numerous in vivo studies have demonstrated that at higher doses MEM attenuates AChE inhibition against several organophosphate (OP) nerve agents (soman, sarin, tabun, and VX), an OP prototype compound (DFP) and an insecticide (methyl parathion), and carbamate insecticides (carbofuran, aldicarb, oxamyl, and methomyl) [Gupta and Kadel, 1989, 1990, 1991Gupta and Dettbarn, 1992;McLean et al, 1992;Gupta, 1994;Gupta and Goad, 2000]. Both in vitro and in vivo studies [McLean et al, 1992;Stojiljkovic et al, 2002;Antonijevic et al, 2002] further confirmed that MEM pretreatment protects AChE in rat and mice brain against soman-induced AChE inhibition.…”
Section: Discussionmentioning
confidence: 64%
“…Memantine (MEM) is a specific, uncompetitive, voltage-dependent NMDA receptor antagonist with low-to moderate-affinity, strong voltage dependency, and rapid blocking/unblocking receptor kinetics and is effective in moderate to severe cases of dementia Reisberg et al, 2003;Wilcock, 2003]. Numerous data demonstrate that at higher doses, MEM induced attenuation of in vitro/in vivo AChE inhibition by organophosphates and carbamates [Gupta and Kadel, 1989, 1990, 1991Gupta and Dettbarn, 1992;McLean et al, 1992;Gupta, 1994]. In an in vitro study, Wenk et al [2000] found no interaction of MEM with AChE inhibitors, including donepezil, tacrine, and galantamine.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the organophosphates, recovery of AChE activity after a carbamate (e.g., carbofuran)-induced inhibition is quite rapid since recovery simply requires the spontaneous hydrolysis of the covalent bond between the methyl carbamyl moiety and the enzyme (Ferguson et al, 1984;Gupta and Kadel, 1989). This observation is also true for several other carbamate pesticides, including aldicarb, methomyl, and propoxur (Gupta, 1994(Gupta, , 2004Gupta and Kadel, 1990, 1991a, 1991b.…”
Section: Effects Of Organophosphates and Carbamates On Acetylcholinesmentioning
confidence: 80%
“…These authors suggested that mAChRs and nAChRs, as well as NMDA receptors, seem to play major roles in anticholinesterase-induced neurotoxicity and that combined treatment with cholinergic and NMDA antagonists might be beneficial in anticholinesterase-induced poisonings (Dekundy et al, 2001(Dekundy et al, , 2003. In similar studies, another NMDA receptor antagonist memantine, in combination with atropine, has been found equally effective against organophosphate and carbamate poisoning (Gupta, 1994;Gupta and Kadel, 1989, 1990, 1991a, 1991bMcLean et al, 1992).…”
Section: Effects On Neuroactivities Other Than the Cholinergic Systemmentioning
confidence: 82%
“…Tom prilikom saopšteno je i da predtretman memantinom smanjuje stepen inhibicije AChE raznih regija mozga i nekih skeletnih mišića kod pacova trovanih somanom. Od strane istih istraživača, usledila su ubrzo i ispitivanja profilaktičkog i terapijskog efekta memantina i atropina kod većeg broja antiholinesteraznih supstanci [26][27][28][29][30][31][32][33][34] .…”
Section: Uvodunclassified